Cost Effectiveness In The Construction Of Terrace Houses By Using Raft Foundation & Concrete Masonry Unit - Chua, Chun How (Universiti Sains Malaysia, 2005)
A research done by the Construction Cost Engineering Research Group of University of Liverpool had shown that the type of foundation has achieved an important index of 71% which indicates a high effect on cost and duration of construction projects. Conventionally, local construction of terrace houses will use pad footing as the foundation. However, raft foundation gradually has gained popularity among the local contractors nowadays in their construction of terrace houses. Even the qualified engineers seem to agree on the statement that the raft foundation is able to bring cost effectiveness compare to pad foundation. Nonetheless, there is no such a survey carried out locally to show the results of both the alternatives in the construction of foundation. Thus, the case studies from this final year project are hopefully able to bring an answer to the question above with a standard design and reliable figure. Concrete masonry unit or in this case, concrete hollow block is an alternative in the construction of walls. It is believed that the material is sooner going to replace the conventional clay brick in wall design. Basically, the concrete hollow block seems to be able to reduce the usage of steel bars and concrete while the formwork and plaster are eliminated in the construction. Concrete hollow block is expected to reduce the cost of a housing project by 30% if compare to brick wall. However, this figure is provided by the contractor from the manufacturer of concrete masonry itself. There is no survey done by either local suppliers or engineers as well as to prove the positive outcome in the context of cost effectiveness by using concrete masonry unit in wall design.